Frailty modeling of cardiovascular risk factors among Filipinos - Peñaranda, Bridith S.
At present, majority of Filipino physicians are aware only of the Framingham list of CVDrisk factors, and usually is the basis in identifying the Filipino patient's risk of heart disease accordingly. Some variances in the Filipino lifestyle and genetic profile may require some modifications on the existing risk equation.This study aims to create a prediction model which can estimate CVD risk among Filipinos based on currently known risk factors using survival analysis. Six out of 13 national regions were included in the cohort. There were 1749 individuals included. Survival techniques specifically Weibull regression model and frailty model were fitted to the data. The study found five risk factors: age, gender, blood pressure, DM, and smoking, significant in predicting death due to cardiovascular disease. The effect of HDL and LDL was not found statistically significant in the model development. Younger female individuals with non-elevated blood pressure, non-diabetics and who do not smoke have a greater chance of survival. A sex-specific model using Weibull distribution was chosen to be the distribution of choice. Incorporating frailty was not needed in this data.